2022
DOI: 10.3389/fpubh.2022.959016
|View full text |Cite
|
Sign up to set email alerts
|

Effects and implementation of a minimized physical restraint program for older adults in nursing homes: A pilot study

Abstract: PurposePhysical restraint (PR) reduction interventions are currently exploring in developed regions with well-established welfare systems, whereas developing countries with fast population aging have not attracted enough attention. This China's pilot study evaluated the effects of a minimized PR program on restraint reduction and nursing assistants' knowledge, attitudes, intention, and practice toward PR and explored nursing assistants' experience of the program.Patients and methodsThis was a one-group, pretes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…Unfortunately, owing to the design and sample of the study, the effectiveness of the interventions was found to be inconclusive. The result was in line with recent studies on the same subject [61,84]. A study assessing the association between surveillance technology and restraint found no significant relationship [68].…”
Section: Discussionsupporting
confidence: 91%
“…Unfortunately, owing to the design and sample of the study, the effectiveness of the interventions was found to be inconclusive. The result was in line with recent studies on the same subject [61,84]. A study assessing the association between surveillance technology and restraint found no significant relationship [68].…”
Section: Discussionsupporting
confidence: 91%
“…Of the 2530 retrieved studies, 193 were ultimately included 6,7,11–201 . The PRISMA-ScR diagram (Figure 1) shows the study selection process and reasons for full-text exclusion.…”
Section: Resultsmentioning
confidence: 99%